Feasibility and Safety of Laparoscopic Radical Colectomy for T4b Colon Cancer at a University Hospital in Vietnam - Nguyen, Bac H.; Le, An N. T.; Le, Kien T.; Tran, Huy D.; La, Duc M.; Thai, Truc T.; Tran, Hung X.; Nguyen, Thinh H.; Pham, Vinh T. N. (BioMed research international, 2020)
Background. The choice of optimal treatment strategies for T4b colon cancers has still been discussed, particularly the initiation of neoadjuvant therapy or surgery. We conducted this study to evaluate the safety and feasibility of laparoscopic multivisceral resection for T4b colon cancers. Methods. We used the retrospective design to include all 43 patients with T4b colon cancer at a university hospital in Vietnam from March 2017 to March 2019. All patients were followed 30 days after the surgery, and information about the day of the first flatus, length of hospital stay, iatrogenic complications, postoperative morbidity, mortality, and adjuvant chemotherapy was collected. Results. The mean operating time was 187 minutes (ranging from 80 to 310), the mean blood loss was 64.3 ml (5-200), and the conversion rate was 2.3%. The mean number of lymph nodes harvested was 15.5 (SD=8.06), and 33 patients (76.7%) had at least 12 lymph nodes harvested. A total of 21 patients (48.8%) had lymph node metastases with a mean number of lymph node metastases of 1.89 (SD=3.4). The radial resection margin was R0 in all 43 patients (100%). The median time until the first flatus and hospital stay were 3 days (2–5) and 7.1 (6–11) days, respectively. There was no mortality at 30 days postoperatively, and one patient had iatrogenic complication (2.3%). Conclusion. Laparoscopic radical colectomy was feasible and safe for patients with T4b colon cancer except those requiring major and complicated reconstruction.